2020
DOI: 10.1101/2020.08.20.259192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibitory control of frontal metastability sets the temporal signature of cognition

Abstract: Cortical neural dynamics organizes over multiple anatomical and temporal scales. The mechanistic origin of the temporal organization and its contribution to cognition remain unknown. Here we demonstrate that a temporal signature (autocorrelogram time constant and latency) of neural activity enlightens this organization. In monkey frontal areas, recorded during flexible cognitive decisions, temporal signatures display highly specific area-dependent ranges, as well as anatomical and cell-type distributions. More… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 74 publications
(127 reference statements)
0
12
0
Order By: Relevance
“…Single-neuron autocorrelograms also significantly vary in their offset, and the importance of this parameter has yet to be explored. One recent study also identified important heterogeneity in the initial time-lag before autocorrelation begins to decay as a function of time (Fontanier et al, 2020 ), a feature which was particularly prominent in cingulate cortex (Murray et al, 2014 ; Cavanagh et al, 2016 , 2018 ; Fontanier et al, 2020 ). Related to the time-lag of autocorrelograms, other studies in rodents have demonstrated diversity in the time-lag of stimulus representations (Harvey et al, 2012 ; Morcos and Harvey, 2016 ; Scott et al, 2017 ).…”
Section: A Diversity Of Timescales At the Single Neuron Levelmentioning
confidence: 98%
See 4 more Smart Citations
“…Single-neuron autocorrelograms also significantly vary in their offset, and the importance of this parameter has yet to be explored. One recent study also identified important heterogeneity in the initial time-lag before autocorrelation begins to decay as a function of time (Fontanier et al, 2020 ), a feature which was particularly prominent in cingulate cortex (Murray et al, 2014 ; Cavanagh et al, 2016 , 2018 ; Fontanier et al, 2020 ). Related to the time-lag of autocorrelograms, other studies in rodents have demonstrated diversity in the time-lag of stimulus representations (Harvey et al, 2012 ; Morcos and Harvey, 2016 ; Scott et al, 2017 ).…”
Section: A Diversity Of Timescales At the Single Neuron Levelmentioning
confidence: 98%
“…Interestingly, the cortical layer may also determine the degree of local connectivity, with neurons in layer III of prefrontal cortex thought to have particularly strong recurrent connections (Goldman-Rakic, 1995;Kritzer and Goldman-Rakic, 1995) reflected by an increase in spine density in prefrontal and parietal cortices relative to early sensory areas (Elston, 2003;Elston et al, 2011;Gilman et al, 2017). Recent studies have leveraged new technologies to demonstrate that task-related working memory activity mainly resides in supragranular layers (Markowitz et al, 2015;Bastos et al, 2018;Finn et al, 2019), providing experimental evidence that recurrent circuitry may be important for generating persistent activity. In future studies, laminar electrode probes may also provide insight into the relationship between neural timescales and cortical layer.…”
Section: Inter-regional Connection Patterns and Cortical Layermentioning
confidence: 99%
See 3 more Smart Citations